FRONTEND DEVELOPMENT IN THE FINAL STUDY MANAGEMENT SYSTEM (SIPEDA) AT THE ENGINEERING FACULTY OF JENDERAL SOEDIRMAN UNIVERSITY - Qotrunnada Oktiriani; Arief Kelik Nugroho; Eddy Maryanto (Jurnal Teknik Informatika (Jutif), 2022)
Frontend is a very important part in system development because it is a communication mechanism between the user and the system, so that it will help users to understand how to use and work an application or system. An attractive frontend is also an important factor to improve the quality and user experience while using an application. The purpose of this research is to build frontend final study management system at the engineering faculty of Jenderal Soedirman University with an attractive and easy-to-use interface to facilitate the academic community in managing the final study process which includes final assignments, comprehensive examination and graduation which can be accessed through the website. The development of the management system of this final study uses the DevOps method where the stages discussed in this study include the planning, development, and deployment. The final study management system login is already connected to the SSO KORI Unsoed. In developing this frontend system, the Laravel framework is used by utilizing the blade templating engine feature and several javascript libraries that can simplify and speed up the system display development process. The results of this study are the final study management system interface that has been adapted to the needs of each system user and is connected to the database and can be accessed on an Unsoed server.